Portfel behawioralny jako alternatywa dla funduszy inwestycyjnych - Kicia, Mariusz (Behavioral Portfolio as an Alternative for Mutual Funds, 2008)
Analysis of heuristic portfolios of individual investors compared with Markowitz minimum variance portfolios and mutual funds portfolios is the subject of the research. The analysis is based on 2001-2007 WSE and Polish mutual funds data. The results show that behavioral portfolios although heuristic may be a successful alternative for market portfolio or mutual funds investing in stocks.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 18, s. 49-58